Re-founding the world : a western testament - Guillebaud, Jean Claude (Algora, 2001)
"[A leading French Christian writer,] Guillebaud leads the search for the Greek, Jewish and Christian roots of our fundamental Western values. . . an erudite and frank analysis of the perverse trends that undermine morality today and calls for a revolutio.